Treacher-Collins Syndrome: A case study - Ezzoubi N; Nejjari M; Dini N; Al Ammari I (International Journal of Scientific Research and Innovative Studies, 2026)
The combination of bilateral choanal atresia and Treacher Collins syndrome is a life-threatening neonatal emergency. We report the case of a female newborn with typical facial dysmorphia and immediate respiratory distress due to airway obstruction. Although urgent surgical correction was performed, the outcome was brain death. This case highlights the serious prognosis of severe neonatal forms and emphasises the critical importance of antenatal diagnosis and multidisciplinary care planned from the delivery room onwards. Keywords: Polymalformative syndrome, Choanal atresia, Mandibular hypoplasia, Oto-mandibular dysostosis Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/573